The interpretation of concept «mother» of poems of Uzbek and German poetry (on the example of poems of Uzbek and German poets) - Sayyora , Tagaeva (International Journal of Psychosocial Rehabilitation, 2020)
This article provides a linguocultural and comparative analysis of the concept of "mother" in the poetry of Uzbek and German poets Toshpolat Ahmad and Wilhelm Arent. In the introductory part, mainly the theoretical foundations of the concept are given. The opinions of several linguists, such as V.Maslova, S.A.Askoldov, A.B.Babushkin, E.S.Kubryakova, who conducted research in this field, were noted. Accordingly, it can be seen that the term concept has been interpreted differently by many researchers. The concept of ‘mother’ is important in all languages.